2017
DOI: 10.1021/acscatal.7b02649
|View full text |Cite
|
Sign up to set email alerts
|

Direct Production of Lower Olefins from CO2 Conversion via Bifunctional Catalysis

Abstract: Direct conversion of carbon dioxide (CO2) into lower olefins (C2 =–C4 =), generally referring to ethylene, propylene, and butylene, is highly attractive as a sustainable production route for its great significance in greenhouse gas control and fossil fuel substitution, but such a route always tends to be low in selectivity toward olefins. Here we present a bifunctional catalysis process that offers C2 =–C4 = selectivity as high as 80% and C2–C4 selectivity around 93% at more than 35% CO2 conversion. This is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
367
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 440 publications
(386 citation statements)
references
References 43 publications
16
367
0
3
Order By: Relevance
“…showed that reaction temperatures of around 400 8Cw ere suitablef or synthesizingl ight olefins. [50,51,56,87,93,95] Optimal temperatures differ between studies, but ah igherO /P ratio was obtained upon increasingt he temperature from 200 to 300 8C. [87] Moreover,C O 2 conversion decreases at temperatures ranging from 100 to 450 8C.…”
Section: Effectsofo Peratingc Onditionsmentioning
confidence: 97%
See 4 more Smart Citations
“…showed that reaction temperatures of around 400 8Cw ere suitablef or synthesizingl ight olefins. [50,51,56,87,93,95] Optimal temperatures differ between studies, but ah igherO /P ratio was obtained upon increasingt he temperature from 200 to 300 8C. [87] Moreover,C O 2 conversion decreases at temperatures ranging from 100 to 450 8C.…”
Section: Effectsofo Peratingc Onditionsmentioning
confidence: 97%
“…[93,[99][100][101] ZrO 2 is sometimes added as at extural and electronic promoter.I nC O 2 hydrogenation to olefins, addingZ rO 2 increases thes tabilityo ft he catalystb yp reventing sintering. The Cu/ZnO/Al 2 O 3 system currently employed for methanol synthesis from mixed syngas exhibitslimited activity in CO 2 hydrogenation, so it is not ag ood candidate.…”
Section: The Catalystsmentioning
confidence: 99%
See 3 more Smart Citations